Flow cytometry remission by Ig light chains ratio is a powerful marker of outcome in multiple myeloma after tandem autologous transplant: a real-life study. Issue 1 (December 2016) - Cordone, Iole; Marchesi, Francesco; Masi, Serena; Summa, Valentina; Pisani, Francesco; Merola, Roberta; Cigliana, Giovanni; Orlandi, Giulia; Gumenyuk, Svitlana; Palombi, Francesca; Romano, Atelda; Spadea, Antonio; et al.
Abstract Background The achievement of complete response (CR) significantly correlates with a better clinical outcome in multiple myeloma (MM) patients treated with autologous stem cell transplant (ASCT). The depth of response is one of the most relevant factors to predict patient's outcome, however the definition of CR through standard criteria has shown several limitations. Methods In this study we evaluated the minimal residual disease (MRD) in 50 consecutive MM patients who underwent an up-front tandem ASCT in our center, using a single-tube six-colors flow cytometry assay (FC) based on intra-cytoplasmic immunoglobulin (cy-Ig) light chains ratio evaluated on patient-specific plasma cells (PC) immune profile, in a real-life setting. Results With a sensitivity up to 10−5, clonal-PC were documented by FC in 36.4 % (12/33) of patients in conventional CR after second transplant. The number of flow MRD-negative patients significantly increased after induction and first ASCT, but not between first and second transplant. The 5-years progression-free survival (5ys-PFS) of flow MRD-negative patients after second transplant was significantly better than patients who remained MRD-positive considering both all patients (5ys-PFS: 70 %vs 5 %) and patients in CR according to standard criteria (5ys-PFS: 67 %vs 0 %). Conclusions FC remission through cy-Ig light ratio on PC sub-populations is a sensitive, highly informative, low-cost and routinely applicable MRD assay, a powerful tool in treatment response evaluation and a crucial marker of outcome in MM.